2008
DOI: 10.1038/bjp.2008.84
|View full text |Cite
|
Sign up to set email alerts
|

Activation of prostaglandin EP receptors by lubiprostone in rat and human stomach and colon

Abstract: Background and purpose: Lubiprostone (Amitiza), a possible ClC-2 channel opener derived from prostaglandin E 1 and indicated for the treatment of constipation, increases chloride ion transport and fluid secretion into the intestinal lumen. As lubiprostone may also directly modulate gastrointestinal motility, we investigated its actions and the possible involvement of prostaglandin EP receptor activation on rat and human isolated gastrointestinal preparations. Experimental approach: Rat and human isolated prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 15 publications
1
79
1
Order By: Relevance
“…Our results do not support the suggestion in the reports of Bassil et al (3,4) that actions of lubiprostone on gastrointestinal motility and perhaps mucosal secretion reflect stimulation of prostaglandin EP receptors. We found that intraneuronal microelectrodes recorded excitatory responses (i.e., membrane depolarization and spike discharge) in submucosal ganglion cells in response to each of three different prostaglandins.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results do not support the suggestion in the reports of Bassil et al (3,4) that actions of lubiprostone on gastrointestinal motility and perhaps mucosal secretion reflect stimulation of prostaglandin EP receptors. We found that intraneuronal microelectrodes recorded excitatory responses (i.e., membrane depolarization and spike discharge) in submucosal ganglion cells in response to each of three different prostaglandins.…”
Section: Discussioncontrasting
confidence: 57%
“…Signal transduction for M 3 -mediated activation of Cl Ϫ secretion involves elevation of Ca 2ϩ in the enterocytes and stimulation of PKC (19). Absence of evidence for opening of ClC-2 channels by elevation of intracellular Ca 2ϩ makes ClC-2 an unlikely candidate for explanation of the enhancing effects of lubiprostone on the muscarinic-evoked first phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true if the lubiprostone is administered prior to bowel cleansing with the agents such as polyethylene glycol electrolyte (PEG-E) [3] . Lubiprostone also enhances and stimulates contraction in colonic as well as gastric muscles and may, thus, further contribute as a prokinetic agent [4] . Besides these effects, lubiprostone also causes hyperpolarization in other tissues such as uterine muscle cells [5] .…”
Section: To the Editormentioning
confidence: 99%
“…33 Lubiprostone also enhances and stimulates contraction in colonic as well as gastric muscles through prostaglandin E receptors, suggesting direct effects on GI motility. 34,35 This drug has been approved by the Food and Drug Administration (FDA) as a treatment for women and men with chronic constipation at a dose of 24 μg, twice daily, and for women with IBS-C at a dose of 8 μg, twice daily. Lubiprostone is contraindicated in mechanical GI obstruction and is FDA pregnancy category C. Lubiprostone has been consistently demonstrated to be superior to placebo for increasing the number of SBMs, improving stool consistency, reducing straining, bloating and overall constipation symptoms in several large, multicenter RCTs involving CC and IBS-C. 23,[36][37][38][39][40] One phase III trial in CC involved 242 patients (average age: 48 years; 89% female; 88% Caucasian) who received either lubiprostone 24 μg twice daily or placebo with food for a period of 4 weeks with a primary efficacy end point of number of SBM at 1 week of treatment.…”
Section: Lubiprostonementioning
confidence: 99%